A study on the relationships between some linear type traits and mastitis in brown-swiss cows - İbrahim Şeker; Ali Rişvanlı; Metin Bayraktar; Selim Kul; Erdal Kaygusuzoğlu (Eurasian Journal of Veterinary Sciences)
This study was conducted to determine the relationships between some linear type traits and mastitis in Brown-Swiss at a dairy (arm in Malatya. Fifty four Brown-Swiss cows at the age of 2 to 8 were included in the study. In the study, front teat placement, front teat lenght, front udder attachment, udder depth, rear udder attachment, suspensory ligament and rear legs (side view) were considered as linear type traits. Furthermore, an overall milking features were evaluated as the final score. The results show that incidence ol mastitis was increased in Brown-Swiss with high udder depth. The rest of the udder traits were not significant factors in relation to mastitis incidence. Additionally, the parameters such as rear legs and final score did not significantly influence the mastitis incidence. A higher incidence of mastitis was noticed in animal with high score of front teat length but the difference between groups was not statistically significant. In conclusion, it might be stated that in selection and breeding of dairy cows, udder depth can be taken into consideration.